Interpretation and Management of Al-Tibb An-Nabawi Learning in Pesantren: A Case Study at Pesantren Sunan Kalijaga Nganjuk Indonesia - Natsir, Ahmad; 'Aziz, Hafidh; Jannana, Nora Saiva (Journal of Islamic Education Management Research, 2024)
Purpose – This study aims to analyze the efforts of pesantren in reconstructing traditional medicine in line with the vision of al-Tibb al-Nabawi and the management of al-Tibb al-Nabawi learning in pesantren. Design/methods– This research uses a case study at Pesantren Sunan Kalijaga Pakuncen Nganjuk, aligned with the mission of education and the development of traditional medicine through the production of traditional herbal medicine. Utilizing an interactive descriptive analysis with Abed al-Jabiri's postcolonial theory Findings – The researcher concludes that Pesantren Sunan Kalijaga interprets Tibb An-Nabawi by combining the principles of prophetic medicine and traditional Nusantara medicine, resulting in effective and affordable health solutions such as Jamu Al-Qomar. The management of learning in this pesantren involves holistic religious education, practical skills, and structured unit business management, equipping students with life skills and independence. Research implications/limitations – The differences in social and cultural contexts between the community around Pesantren Sunan Kalijaga and communities in other regions of Indonesia could influence the results of this study. Practices and acceptance of traditional medicine and al-Tibb al-Nabawi can vary greatly in different places. Practical implications – This research establishes a foundation for enhancing healthcare services in pesantrens by integrating Al-Tibb An-Nabawi with local traditional medicine, promoting economic self-sufficiency through herbal enterprises like those at Pesantren Sunan Kalijaga. The life skills education methods can be adopted to equip students with practical skills. Originality/value – This research offers a novel perspective on integrating Al-Tibb An-Nabawi with traditional Nusantara medicine in pesantrens, specifically at Pesantren Sunan Kalijaga. It highlights a unique life skills education model combining religious education with practical health and herbal medicine skills, providing an innovative example for healthcare and economic self-sufficiency in other pesantrens